Jewish responses to persecution, 1933-1946 : a source reader - Matthäus, Jürgen 1959- (Documenting life and destruction, 2017)
This reader combines primary sources from many archival collections with contextual background on key aspects of Jewish life during the Holocaust. It calls into question prevailing perceptions of Jews as a homogenous, faceless, or passive mass of victims, helping to complicate student understanding of the complexities inherent in Holocaust history.